Analysis The Effect of Coconut Shell Charcoal Mixed Doses and Adhesive In Characteristics Jamu Dregs Briquettes - Arafah, Arinda Dwi; Harsono, Soni Sisbudi (BERKALA SAINSTEK, 2021)
Briquette is an alternative simple fuel that has a relatively high calorific value, so it has the potential to reduce the use of firewood and fuel oil (BBM). Herbal waste is one of the biomass materials that came from the rest of the material in the production of herbal medicine made from medicinal plants. Utilization of herbal dregs as briquettes has been implemented by PT. Industri Jamu dan Farmasi Sido Muncul. Tbk, as fuel for boiler engines. Making briquettes from biomass requires the addition of materials, one of which is coconut shell charcoal and adhesives such as molasses and tapioca flour to improve the physical properties of the briquettes. Briquettes with good quality have a maximum moisture content and ash content of 8%, a heating value of more than 5000 cal/gram, a constant combustion temperature of 350℃ for a long period of time and is easily flammable. The purpose of this study was to determine the characteristics of briquettes based on the value of water content, ash content, combustion temperature, combustion rate, and calorific value. Variable treatment with the addition of coconut shell charcoal with several doses of 10%, 20%, and 30% and variations of adhesive materials. Data analysis was performed by using two-factor ANOVA statistical test. The results showed that briquettes with tapioca flour adhesive and 30% coconut shell charcoal composition had the best characteristics of briquettes compared to other variations.